2017
DOI: 10.14338/ijpt-17-00008.1
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable Ameloblastoma Successfully Treated with Definitive Proton Therapy

Abstract: We report the case of an 87-year-old man affected by an unresectable ameloblastoma of the right jaw that was successfully treated by definitive proton therapy up to a dose of 66 Gy in 33 fractions. Treatment was well tolerated, and there were no interruptions due to toxicity. At follow-up visits, the patient experienced complete response to treatment with no evidence of disease and complete recovery from acute side effects. In this report, we discuss the potential and possible pitfalls of proton therapy in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Therefore, such a challenging treatment could be better tolerated by heavily pretreated patients. Patients' compliance with concomitant chemotherapy could also increase; moreover, elderly patients could be considered for reirradiation [43,44]. As of outcome, a recent report by Yamzaki et al [45] regarding the results of particle or X-ray reirradiation for HN patients showed a statistically significant better OS in patients treated with particle therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, such a challenging treatment could be better tolerated by heavily pretreated patients. Patients' compliance with concomitant chemotherapy could also increase; moreover, elderly patients could be considered for reirradiation [43,44]. As of outcome, a recent report by Yamzaki et al [45] regarding the results of particle or X-ray reirradiation for HN patients showed a statistically significant better OS in patients treated with particle therapy.…”
Section: Discussionmentioning
confidence: 99%